Calculation of vibrations in the early design phase - Rasmark, Nils; Hellquist, Fredrik (My University, 2018)
Buildings exposed to vibrations from heavy road or train traffic do not normally risk being damaged, but the vibrations can cause discomfort to the users. Performing a detailed dynamic analysis is expensive and time consuming. Consequently, they are rarely performed with regard to comfort vibrations. Fagerström and Lindorsson (2017) studied a simple method of analysing beams and frame structures with respect to comfort vibrations. As a continuation of their work, this thesis aims to further develop a simple and effective method for studying comfort vibrations of buildings by incorporating plates into the method. In addition, it is investigated if the vibration of a plate can be predicted by interpolation of the known vibrations of similar plates. A calculation program in MATLAB is developed where the simplified analyses can be performed. The results are compared to analyses performed with a commercial FE program. The study shows a large spread in the results between the simple and the more advanced method. The behaviour of plates are more complicated than beams and requires a higher understanding to be able to interpret the results correctly. If one takes careful measures with regards to the mesh, the dominant frequency range of the applied response spectrum and the natural frequencies of the studied plates, the simplified method provides results with reasonable accuracy. The study also shows that an interpolation between plates with similar geometry and boundary conditions to obtain the response is not easily performed, due to relatively small parameter differences potentially causing profound changes in the behaviour.
Keywords: Building Futures; Samhällsbyggnadsteknik; Teknisk mekanik; Building Futures; Civil Engineering; Applied Mechanics